(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
This article is devoted to the typology of German language electronic dictionaries and contains scientific conclusions. In this regard, great Uzbek and German lexicographers were presented and existing dictionaries created on their basis were analyzed. At the same time, it serves to increase the knowledge of the dictionaries involving orthographic, orthoepic, anthroponomic, toponymic, synonymic, frequency, dialectological, historical, international words, inverse and etymological in these languages, where no research has been done.